P767 Imagiologic features and Prevalence of Cardiac Lesions detected in Transesophageal Echocardiography. (17th January 2020) - Pereira Oliveira, I; Neto, A; Seabra, D; Cruz, I; Abreu, G; Pereira, A; Azevedo, J; Pinto, P
Abstract: INTRODUCTION: Echocardiography plays a central role in the detection of intracardiac lesions, with transesophageal echocardiography (TEE) acquiring an outstanding role due to its increased sensitivity, improving diagnosis and evaluation of complications. PURPOSE To characterize clinically and echocardiographically the type of intracardiac masses mostly identified on TEE, in order to reflect about its prevalence, exam indication and echocardiographic criteria for correct diagnosis. METHODS: Unicentric, retrospective observational analysis of TEE examinations performed between 01/2014 and 05/2019. Data collected from TEE registers and patient process assessment. Cardiac findings were classified according to its echocardiographic features as vegetations, thrombi or suspected tumoral masses. RESULTS 144 TEE examinations revealed the presence of intracavitary lesions, with 62% of them (89 exams) having imagiologic features suggestive of vegetations, with polypoid highly mobile lesions attached to valve leaflets, often leading to valvular insufficiency. More than one valve was affected in 21% and about 30% were prosthetic valves. Potential serious complications such as perforation and abscess formation were present in 13% and 7%, respectively. 35 examinations disclosed the presence of thrombi, 66% located on the left atrial appendage and 17% on the left atrium (LA). In 4 cases they were attached to prosthetic valves and 10 of the patients had not been anticoagulated previously. Some doubtful diagnosis were lately confirmed after disappearance of the lesion with anticoagulation therapy. Diagnosis of tumoral masses was made in 11%, some of them waiting for histologic confirmation. 50% had features resembling pappilary fibroelastomas (PF) (38% of the aortic valve, 25% of the mitral valve, 1 of the pulmonary valve and 1 the left ventricle pathologically confirmed), such as a filiform highly mobile pedunculated structure attached to a valve leaflet. Heterogeneous masses suggestive of myxomas were identified in 35%, 80% located on the LA. The most frequent reason for performing a TEE examination was a previous embolic event, a doubtful image on transthoracic echocardiogram or before electrical cardioversion. Except for PF which were increasingly detected by echocardiography, the prevalence of thrombi or vegetations remained similar across the years. Most presumptive diagnosis made by TEE were confirmed based on clinical evolution or histology. CONCLUSIONS: In this cohort, most TEE examinations revealed the presence of vegetations, a major criterion for establishing the diagnosis of infective endocarditis. TEE enables more accurate evaluation of the lesions and although histologic confirmation is frequently necessary, some imagiologic features allow for a presumptive diagnosis which is often correct. This analysis also reflects the prevalence of cardiac lesions and the increased awareness of some conditions, such as PF.